2023
DOI: 10.1021/jacs.3c05626
|View full text |Cite
|
Sign up to set email alerts
|

Multielectron Redox Chemistry of Uranium by Accessing the +II Oxidation State and Enabling Reduction to a U(I) Synthon

Abstract: The synthesis of molecular uranium complexes in oxidation states lower than +3 remains a challenge despite the interest for their multielectron transfer reactivity and electronic structures. Herein, we report the one-and two-electron reduction of a U(III) complex supported by an arene-tethered tris(siloxide) tripodal ligand leading to the mono-reduced complexes, [K(THF)-U((OSi(O t Bu) 2 Ar) 3 -arene. EPR and UV/vis/NIR spectroscopies, magnetic, cyclic voltammetry, and computational studies provide strong evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 69 publications
5
24
0
Order By: Relevance
“…Each uranium ion is also bound by two additional bridging anionic siloxide oxygens from an adjacent U( iBu POSS) unit. The U–O siloxide distances range from 2.125(16) Å to 2.568(17) Å (average value of 2.36(2) Å), which lie within the range of distances found in previously reported U( iii ) siloxide complexes 28,36,37 (2.182(3)–2.549(3) Å). The U 3 ( μ -O) 6 core in 1 displays alternating U–O bond lengths in which the shortest bonds are observed for an anionic oxygen from the coordinated iBu POSS (U1–O1, U2–O13 and U3–O25) and for two bridging anionic oxygens from an adjacent U( iBu POSS) fragment (U1–O35, U1–O36, U2–O11, U2–O12, U3–O23, U3–O24), thus ensuring the trimeric architecture's rigidity (Fig.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Each uranium ion is also bound by two additional bridging anionic siloxide oxygens from an adjacent U( iBu POSS) unit. The U–O siloxide distances range from 2.125(16) Å to 2.568(17) Å (average value of 2.36(2) Å), which lie within the range of distances found in previously reported U( iii ) siloxide complexes 28,36,37 (2.182(3)–2.549(3) Å). The U 3 ( μ -O) 6 core in 1 displays alternating U–O bond lengths in which the shortest bonds are observed for an anionic oxygen from the coordinated iBu POSS (U1–O1, U2–O13 and U3–O25) and for two bridging anionic oxygens from an adjacent U( iBu POSS) fragment (U1–O35, U1–O36, U2–O11, U2–O12, U3–O23, U3–O24), thus ensuring the trimeric architecture's rigidity (Fig.…”
supporting
confidence: 82%
“…Complex 2 displays a moderate and monotonic decrease of its magnetic moment to reach a value of 4.35 μ B (2.51 μ B per uranium centre) at 15 K before dropping to 3.58 μ B (2.07 μ B per uranium centre) at 2 K. The observed behaviour is similar to those measured for mononuclear complexes of U( iii ) suggesting that the three uranium centres in 2 are essentially magnetically independent. 37,45,46…”
mentioning
confidence: 99%
“…In order to further investigate the reduction degree of N 2 in complexes 1 , 2-THF , DFT calculations were carried out using the B3PW91 functional that has been successfully used to describe similar complexes in the past . For complex 1 , three different spin states were computed and the quintet is found to be the ground state, with the triplet and singlet being higher in energy (8.7 kcal/mol –1 and more than 45 kcal/mol –1 , respectively).…”
Section: Resultsmentioning
confidence: 99%
“…However, the low stability of cerium(II) and the large disparity among different oxidation states prevented the implementation of two-electron processes at a single cerium center. Recently, metal–arene interaction has been shown to play a key role in stabilizing low-valent f-block metal centers and enabling electrocatalytic water reduction. ,, Herein, we report the stabilization of three oxidation states of cerium, +2 to +4, by a tripodal tris(amido)arene ligand and the two-electron oxidation of the cerium(II) ion by pyridine N-oxide or an aryl azide to yield cerium(IV) terminal oxo or imido complexes, respectively. Spectroscopic and magnetic characterization together with density functional theory (DFT) calculations showed that the cerium(II) ion is best described as a 4f 2 ion stabilized by δ-interactions with the anchoring arene of the tripodal ligand.…”
Section: Introductionmentioning
confidence: 99%